2006
DOI: 10.1007/s00253-005-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance and microbial dynamics of an up-flow fixed bed reactor established for the biodegradation of fluorobenzene

Abstract: An up-flow fixed bed reactor (UFBR) was established to investigate the biodegradation of fluorobenzene (FB) under a number of operating conditions, which included variation in the concentration of FB in the feed stream (up to 180 mg l(-1)) and temporary suspension of feeding. Degradation of FB was followed for a period of 8 months under a continuous flow regime. During the operation of the UFBR, FB was never detected in the reactor effluent, being biodegraded by the microbial biofilm or adsorbed to the granula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 34 publications
4
25
0
Order By: Relevance
“…This stability was reflected functionally as the MCB reactor exhibited excellent functional performance throughout (Emanuelsson et al, 2005). Analogous long-term stability was observed in other studies on biodegradation of 1,2-dichloroethane, fluorobenzene and 2-fluorobenzoate, although in these cases the associated communities were rather stable (Baptista et al, 2006;Carvalho et al, 2006;Emanuelsson et al, 2006). In the case presented here, the community displayed a dynamic behaviour, which could reflect the interactions between the established community and incoming species.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This stability was reflected functionally as the MCB reactor exhibited excellent functional performance throughout (Emanuelsson et al, 2005). Analogous long-term stability was observed in other studies on biodegradation of 1,2-dichloroethane, fluorobenzene and 2-fluorobenzoate, although in these cases the associated communities were rather stable (Baptista et al, 2006;Carvalho et al, 2006;Emanuelsson et al, 2006). In the case presented here, the community displayed a dynamic behaviour, which could reflect the interactions between the established community and incoming species.…”
Section: Discussionsupporting
confidence: 67%
“…For instance, these techniques have, surprisingly, revealed that functionally stable bioreactors could maintain highly dynamic communities (Fernandez et al, 1999;Zumstein et al, 2000). The application of these techniques has now become essential for complex communities studies and, particularly, for monitoring the progress of specific strains in biotreatment technologies (Baptista et al, 2006;Carvalho et al, 2006;Koutinas et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…While the initial change in bacterial community could be attributed naturally to the adaptation of the seeded activated sludge to new operational conditions in the reactor, the stable communities established with further reactor operation might be ascertained through incorporating other factors specific to the reactor system. Stable microbial communities have been found in engineered biofilm reactors under constant condition [5,12]. Compared to suspension microbial communities, biofilm microorganisms are tolerant of fluctuations in environmental conditions and resilient to minor perturbations as the physical habitat provides some buffering of environmental fluctuations [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…1 Its use as support material in carrier-assisted biofilm reactors has been successfully demonstrated for the treatment of wastewaters containing many different toxic compounds (e.g., containing 2-fluorobenzoate 58 ; fluorobenzene 31,32 ; methyl tertbutyl ether; 4-chlorophenol 30 ; benzene, toluene, ethylbenzene, and xylene (BTEX) 174 ; PCP 104 ; phenol, p-nitrophenol, and phenanthrene 1 ; and atrazine and simazine 64 ).…”
Section: Eps and Biosorption In Biofilm Reactorsmentioning
confidence: 99%